The correct answer is: 3) " x ; 1/2" .
_____________________________________________________
Explanation:
_____________________________________________________
Question 1)
g [ f(x) ] = ? ;
→ Given: " f(x) = 1/3 x " ;
→ Given: " g(x) = 3x " ;
__________________________________
g [ f(x) ] = g(1/3 x) = 3(1/3 x) = 1x = "x" .
__________________________________
Question 2)
g [ f(1/2) ] = ? ;
__________________________________
→ Given: " f(x) = 1/3 x " ;
→ f(1/2) = (1/3) * (1/2) = (1*1) / (3*2) = (1/6) ;
→ g [ f(x) ] =
g(1/6) = 3* (1/6) = (3/1) * (1/6) = (3*1) / (1*6) = 3/6 = (3÷3) / (6÷3) = " 1/2 " .
___________________________________________________________
The first differences are 8, 14, 20.
The second differences are 6.
Half of 6 is 3, so the first term of the sequence is 3n^2.
If you subtract 3n^2 from the sequence you get 0,-1,-2,-3 which has the nth term of -n + 1.
Therefore your final answer will be 3n^2 - n + 1
Answer:
x = 0.5
Step-by-step explanation:
hope this helps!
Golden retrievers: 12/32
poodles: 20/32
does it need to be simplified?